Climate Change Education, Globalisation and the Nation State: A Commentary on Ghana’s Science Curriculum - Christian Konadu Asante; Edward Yalley; Gideon Amissah (Australian Journal of Environmental Education)
In this paper, we offer a commentary on the climate change content in Ghana’s primary and junior high school science curriculum. Since 2019, the government of Ghana has mandated climate change education at multiple levels of the school system. However, there is very little analysis of these curricula. This paper fills an important gap by critically reviewing the climate change content in the science curriculum in a country with a complex and tenuous past regarding capitalist and colonialist expansion and exploitation. We note that while the curriculum attends to technical details of greenhouse gas emissions and climate impacts, it elides the larger global context that has led to the rise in carbon emissions and anthropogenic climate change. We make the case for a climate change curriculum that integrates culture, language and histories, and tackles the complexities of globalisation.